2004
DOI: 10.1136/tc.2004.008169
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking using a waterpipe: a re-emerging strain in a global epidemic

Abstract: Context:The global tobacco epidemic may kill 10 million people annually in the next 20–30 years, with 70% of these deaths occurring in developing countries. Current research, treatment, and policy efforts focus on cigarettes, while many people in developing regions (Asia, Indian subcontinent, Eastern Mediterranean) smoke tobacco using waterpipes. Waterpipes are increasing in popularity, and more must be learned about them so that we can understand their effects on public health, curtail their spread, and help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
416
3
22

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 454 publications
(451 citation statements)
references
References 56 publications
10
416
3
22
Order By: Relevance
“…Links have been made to many of the same adverse health effects, including lung, oral and bladder cancer, as well as clogged arteries and heart disease. 7 An analysis of mainstream smoke from waterpipes found that it contains significant amounts of nicotine, tar and heavy metals. 8 A study of nicotine and cotinine (a chemical marker of nicotine exposure) levels in hookah smokers found high amounts of both chemicals after one session of hookah use.…”
Section: State Of the Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Links have been made to many of the same adverse health effects, including lung, oral and bladder cancer, as well as clogged arteries and heart disease. 7 An analysis of mainstream smoke from waterpipes found that it contains significant amounts of nicotine, tar and heavy metals. 8 A study of nicotine and cotinine (a chemical marker of nicotine exposure) levels in hookah smokers found high amounts of both chemicals after one session of hookah use.…”
Section: State Of the Sciencementioning
confidence: 99%
“…Shared mouthpieces and the heated, moist smoke may enhance the opportunity for such diseases to spread. 13 Also, although limited research has been done in this area, the secondhand smoke from a waterpipe is potentially dangerous because it contains smoke from the tobacco itself as well as the smoke from the heat source used to burn the tobacco. 14 More investigation is certainly needed to determine the health effects of both long-and shortterm waterpipe use, as well as the relative risk of waterpipe use compared to other forms of tobacco use.…”
Section: State Of the Sciencementioning
confidence: 99%
“…Enfin, le CO a été choisi parce que sa mesure avec des capteurs portables est relativement fiable et facile à réaliser. Plusieurs travaux montrent que les teneurs en CO mesurées dans les bars à chicha sont relativement élevées [4,16,17]. Ces études, basées essentiellement sur une comparaison avec les émissions dues aux cigarettes, montrent quelques disparités : d'après l'OMS [4], une séance d'un fumeur de narguilé peut l'exposer à un volume de fumée correspondant à celui émis par un nombre de cigarettes compris entre 40 et 100.…”
Section: Matériel Et Méthodeunclassified
“…D'autres mesures montrent que l'augmentation du monoxyde de carbone expiré à la fin d'une session de chicha est équivalente à celle observée lors de la consommation de 30 à 40 cigarettes [17]. Thomas Eissenberg, Professeur de psychologie à l'Université de Virginia Commonwealth, écrit qu'une session durant approximativement 45 minutes délivre 15 fois plus de monoxyde de carbone, qu'une seule cigarette [16]. Au-delà des divergences entre ces résultats, qui traduisent surtout des protocoles de mesure hétérogènes, il apparaît que dans tous les cas la chicha est à l'origine d'une forte pollution au CO. Les vingt « campagnes » de mesures effectuées à Paris montrent des teneurs en CO relativement élevées.…”
Section: Matériel Et Méthodeunclassified
See 1 more Smart Citation